2010
DOI: 10.2298/tsci1001235l
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical-experimental determining of cooling time (t8/5) in hard facing of steels for forging dies

Abstract: This paper investigates the accuracy of analytical, empirical, and numerical expressions, i. e. the most favourable methods for calculating the cooling time from 800 to 500?C (t8/5). The degree of accuracy of time t8/5 is very significant, because it determines the cooling rate, and consequently the structural changes in heat affected zone for hard faced layers. Based on the presented results, one can conclude that the finite element method provides the best conformity with the experiment and among analytical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 1 publication
3
27
0
1
Order By: Relevance
“…These readings depend on austenitization temperature, period of In order to ensure that the accepted procedure and weld regime lead to appropriate structure and mechanical properties (optimal toughness, hardness, and microstructure), besides the already described experimental methods, diagrams of continual cooling in welding conditions were used. Thus, the concordance of experimental and theoretical results was confirmed [4,16,17]. 4).…”
Section: Estimation Of Weldability On the Basis Of Transformation Consupporting
confidence: 54%
See 2 more Smart Citations
“…These readings depend on austenitization temperature, period of In order to ensure that the accepted procedure and weld regime lead to appropriate structure and mechanical properties (optimal toughness, hardness, and microstructure), besides the already described experimental methods, diagrams of continual cooling in welding conditions were used. Thus, the concordance of experimental and theoretical results was confirmed [4,16,17]. 4).…”
Section: Estimation Of Weldability On the Basis Of Transformation Consupporting
confidence: 54%
“…Based on experimental results and references [4,[16][17][18][19], it has been confirmed that the computed cooling time, in a critical temperature interval, can be most accurately calculated using Japanese authors' formula [15]. In this way, the cooling rate can be determined accurately enough without expensive and time-consuming experimental procedures, which means that the aim of this investigation has been achieved.…”
Section: Estimation Of Weldability On the Basis Of Transformation Conmentioning
confidence: 60%
See 1 more Smart Citation
“…For a long time numerous experimental and numerical studies have been dealing with different aspects of the problem, [1][2][3][4][5]. The model is most often a plate with the heat source moving along one axis with constant velocity.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of this paper is to optimize and obtain the best solution for thickness of concrete and VATRAMIL ® GM 22 layers within the insulation wall of the tank, by application of PAK-T [9] software package, which is based on finite element (FE) method and heat conduction laws [10][11][12][13]. Requested condition is to prevent liquid aluminum to cool down below 750 o C after 8 h, as well as to keep the temperature of the outer layer made of S235JRG2 steel below 100 o C. Coefficients of conduction of insulation materials are changing with the temperature, what is taken into account.…”
Section: Introductionmentioning
confidence: 99%